Modernization of medicine in the ottoman empire and its effects on forensic sciences - Ferat Buran; Erdem Özkara (Wolters Kluwer Medknow Publications, 2018)
Modernization in medicine began in the Ottoman Empire in the 19th century. Until that time, medical education had been provided through the traditional master-apprentice practices and its methods had relied on custom or religion. The most important of these reforms was in 1827, when the first medical schools in surgical and clinical branches were opened in İstanbul. The lack of contemporary understanding in medical education until that time had caused an underdevelopment in forensic sciences as it had in various other fields. Following the reform movements, the contents of the forensic medicine curriculum, mainly influenced by the French medical schooling, touched upon all areas of forensic sciences such as pathology, toxicology, organic chemistry, neuropsychiatry, gynecology, handwriting analysis and criminalistics. It was noteworthy to see such rapid development in scientific modernization considering the fact that, before the reform movements, the religion had a repressive effect and it was forbidden to even perform laboratory tests or examinations on corpses. In the modern Turkish Republic, founded in 1923 after World War I, scientific reforms gained momentum and began competing with the modern world. Such that, after a letter sent to the Turkish Government by Albert Einstein in 1933, the contemporary Turkish universities embraced the scientists who escaped from the Nazi regime.